Encyclopedia of glass science, technology, history, and culture - Richet, Pascal (Wiley : American Ceramic Society, 2021)
"The Encyclopedia does not aim at reviewing highly specialized information but at providing a wide readership with a scholarly guidance to the current literature on the most varied aspects of the making, uses and history of glass. In preamble, a general introduction first presents fundamental (but not widely known) features of glass and then turns to basic concepts of glass science. The Encyclopedia proper is made up of ten sections that successively deal with industrial glassmaking, glass structure, physical, transport and chemical properties, interactions with light, inorganic glass families, organically related glasses, environmental and other issues, and finally with the history of glass in a broad sense. As made clear by the section introductions, chapters are arranged in a logical order to ensure overall consistency and avoid useless repetitions, and they also address newly investigated topics to ensure that the Encyclopedia remains a reference work for many years to come. As a conclusion, important recent advance are reviewed by C.A. Angel in the form of a personal retrospective"-- Provided by publisher.
Keywords: Glass -- Encyclopedias.; Glass manufacture -- Encyclopedias.; elektronické knihy; electronic books